PENGARUH PENDIDIKAN ISLAM TERHADAP PEMBENTUKAN KEPRIBADIAN REMAJA DI ERA GLOBALISASI - Usman, Usman (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2024)
Islamic education has an important role in shaping the personality of adolescents, especially in the era of globalisation which is characterised by the rapid flow of information and changes in social values. This study aims to analyse the influence of Islamic education on the character and personality formation of adolescents in Indonesia. Using a qualitative approach and quantitative data, this study collected information from various sources, including surveys, interviews and literature studies. Results show that Islamic education not only provides a moral and ethical foundation, but also helps adolescents in facing the challenges of globalisation. Through education based on Islamic values, adolescents can develop a strong self-identity, increase their sense of tolerance, and build a positive attitude towards differences